Handling Nutrition in Stunted Children Through Education and Family Education in Madura, Indonesia - Zakiyah Yasin; Ahmad Nawawi; Aulia Aprilita Sofiyana; Eka Febriyanti (Knowledge Dynamics, 2024)
Background: Stunting is a public health problem that is associated with an increased risk of morbidity, death and obstacles to both motor and mental growth. This research aims to determine the effect of family education on maternal nutritional behavior for toddlers who experience stunting in Madura, Indonesia. Method: The type of research was quantitative analytical observational, the research design used in this research is Quasi Experimental with a Two Groups Pre-test Post-test with Control Group Design. The population is all stunted toddlers who were registered at the Community Health Center in Madura Indonesia, totaling 78 children and their mothers. The sample was 65 people using simple random sampling technique consisting of 33 control groups and 32 treatment groups. Data collection uses a questionnaire. The variables studied are the incidence of stunting in toddlers as the dependent variable and the independent variable is the mother's nutritional behavior. Result: The research results of the Wilcoxon test analysis showed that there was a significant influence on the average score of maternal nutritional behavior before and after being given family education, with a p-value of 0.001 , namely p<0.05. Conclusion: There is an influence of family education on maternal nutritional behavior for toddlers who experience stunting in Madura Indonesia.